Nitrospira dominant pin-point flocs with granule-like settleability in stirred tank reactors with oxic/hypoxic/oxic zones - Aqeel, Hussain; Asefa, Bruke; Liss, Steven N. (Frontiers in Microbiology, 2023)
The characteristics of biomass and microbial community dynamics, in relation to autotrophic nitrification, were studied in two 20L stirred tank reactors (STR) with oxic/hypoxic/oxic zones. The bioreactors were fed with synthetic wastewater with stepwise increasing ammonia concentrations (50-200 N mg/L) without organic substrate in the first phase (autotrophic phase) for 35 days (R1) and 15 days (R2), followed by a heterotrophic phase (with supplementation of organic substrate). The settling properties of the biomass, represented by pin-point flocs, gradually improved in both reactors during the autotrophic phase. The pin-point flocs of R1 exhibited granule-like settling properties. The SVI30 in RI gradually improved to 29 ml/g MLSS, and the corresponding SVI30/ SVI10 gradually improved to 0.88 during the autotrophic phase. The settling properties of the biomass deteriorated in both bioreactors during the heterotrophic phase. The protein to polysaccharide ratio (PN:PS ratio) gradually increased in the extracted EPS (in both, loosely bound (LB) and tightly bound (TB) EPS) during the autotrophic phase, in both bioreactors. The TB:LB EPS ratio was higher when the pinpoint flocs of R1 showed granule-like settling properties, followed by a decline in TB:LB EPS ratio during the heterotrophic phase. A combination of molecular approaches (droplet digital-PCR (dd-PCR) and 16S rRNA gene sequencing) revealed that Nitrospira were the predominant nitrifying bacteria in the pin-point flocs that show granular sludge-like settling properties during autotrophic phase in R1. Comammox Nitrospira was the dominant ammonia oxidizer in seed biomass and at low ammonia concentrations in both bioreactors. The relative abundance of canonical ammonia-oxidizing bacteria increased with an increase in influent-ammonia concentrations.